Evolution of the Marrow Adipose Tissue Microenvironment - Craft, Clarissa S. (Calcif Tissue Int, 2016)
Adipocytes of the marrow adipose tissue (MAT) are distributed throughout the skeleton, are embedded in extracellular matrix, and are surrounded by cells of the hematopoietic and osteogenic lineages. MAT is a persistent component of the skeletal microenvironment and has the potential to impact local processes including bone accrual and hematopoietic function. In this review, we discuss the initial evolution of MAT in vertebrate lineages while emphasizing comparisons to the development of peripheral adipose, hematopoietic, and skeletal tissues. We then apply these evolutionary clues to define putative functions of MAT. Lastly, we explore the regulation of MAT by two major components of its microenvironment, the extracellular matrix and the nerves embedded within. The extracellular matrix and nerves contribute to both rapid and continuous modification of the MAT niche and may help to explain evolutionary conserved mechanisms underlying the coordinated regulation of blood, bone, and MAT within the skeleton.